Investigation of structural, electronic and optical properties of two-dimensional MoS2-doped-V2O5 composites for photocatalytic application: a density functional theory study - Muhammad Hasnain Jameel, Muhammad Hasnain Jameel; Roslan, Muhammad Sufi; Mayzan, Mohd Zul Hilmi; Agam, Mohd Arif; Zaki I. Zaki, Zaki I. Zaki; Ahmed M. Fallatah, Ahmed M. Fallatah (royal society publishing, 2023)
In the present research, the structural, electronic and optical properties of transition metal dichalcogenide-doped transition metal oxides MoS2-doped-V2O5 with various doping concentrations (x = 1–3%) of MoS2 atoms are studied by using first principles calculation. The generalized gradient approximation Perdew–Burke–Ernzerhof simulation approach is used to investigate the energy bandgap (Eg) of orthorhombic structures. We examined the energy bandgap (Eg) decrement from 2.76 to 1.30 eV with various doping (x = 1–3%) of molybdenum disulfide (MoS2) atoms. The bandgap nature shows that the material is a well-known direct bandgap semiconductor. MoS2 doping (x = 1–3%) atoms in pentoxide (V2O5) creates the extra gamma active states which contribute to the formation of conduction and valance bands. MoS2- doped-V2O5 composite is a proficient photocatalyst, has a large surface area for absorption of light, decreases the electron-hole pairs recombination rate and increases the charge transport. A comprehensive study of optical conductivity reveals that strong peaks of MoS2-doped-V2O5 increase in ultraviolet spectrum region with small shifts at larger energy bands throug